Uji Aktivitas Antioksidan Ekstrak Etanol Daun Balaroa (Kleinhovia hospita L.) Menggunakan DPPH - Uci Edy; Supriadi Supriadi; Anang Wahid Muhammad Diah; Minarni Rama Jura (Media Eksakta, 2023)
To test the antioxidant activity of the ethanol extract of balaroa leaves (Kleinhovia hospita L) using the compound DPPH (2,2-diphenyl-1-pikrilhidrazil) as a provider of free radicals. This study aims to describe the strong, moderate or weak antioxidant activity of balaroa leaf extract. Balaroa leaf powder was extracted by maceration using absolute ethanol as a solvent. Testing the antioxidant activity of balaroa leaf extract was carried out with various concentrations of 20 ppm, 40 ppm, 60 ppm, 80 ppm, and 100 ppm. The antioxidant activity of balaroa leaf extract was analyzed using a UV-Vis spectrophotometer at a wavelength of 517 nm. The results obtained showed that the IC50 value of balaroa leaf extract was 145.211 ppm while the vitamin C reference solution was 4.909 ppm. Based on the IC50 value data, it can be determined that the ethanol extract of balaroa leaves is a moderate antioxidant.